DETERMINANT FACTORS AFFECTING CONSUMER DECISIONS IN PURCHASING SMARTPHONES - Indra Jaya; Yuliani Yuliani (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The research aims to examine the determinants that influence the decision to buy a smartphone. Several factors there are product quality, price, market, promotion were examined to prove the purchase decision and show the effects of the consumer decision in buying a Samsung Galaxy smartphone in Bandar Lampung city. This study uses questionnaire data of respondents. The analysis method in this study uses the Partial Least Square analysis method (PLS). The findings of this study reveal that the low level of purchase decisions Samsung Galaxy smartphones can be damaged by good product quality, more affordable prices for consumers, ease when making pre-orders in the marketplace and attractiveness as well as power promotion of brand ambassadors.